Relationship between retinal capillary vessel density of OCT angiography and intraocular pressure in pig - Mihyun Choi (Nature Portfolio, 2021)
Abstract The purpose of this study was to evaluate density change in the retinal capillary plexus during intra ocular pressure (IOP) elevation in vitrectomized pigs’ eyes using optical coherence tomography angiography (OCTA). Eight eyes of eight micro pigs received vitrectomy and the IOP was controlled from 15 mmHg (baseline) to 105 mmHg in 15 mmHg increments using a vented-gas forced-infusion system, and then decreased back to normal IOP (recovery state). The spectral-domain OCTA device was set to scan an area of 8.8 × 4.4 mm (30° × 15°) above the optic nerve head for each IOP. The relative vessel density (rVAD) compared to baseline was determined for the total retinal blood flow (RBF) which included major retinal artery and venous vessels, radial peripapillary capillaries (RPCs), superficial (SVP), intermediate (IVP), and deep vascular plexus (DVP). The mean rVAD was 0.890 in RBF, 0.826 in RPCs, 0.817 in SVP, 0.819 in IVP, and 0.794 in DVP at 30 mmHg. While the rVAD of RBF and RPCs decreased to 0.504 and 0.541 at 45 mmHg, the SVP, IVP, and DVP decreased to 0.433, 0.359, and 0.345, respectively. When IOP was normalized, the rVAD was recovered in all layers and the VAD of RBF, IVP, and DVP were higher than baseline (P = 0.040, 0.019, and 0.019, respectively). Retinal capillary density deterioration in each layer was found from 30 mmHg using an OCTA system which showed excellent depth-resolved segmentation of retinal capillary layers even at higher IOPs. Reduction in VAD showed full recovery after IOP normalization.